Enhancing English Speaking Skills Through Blended Learning: A Study on Medical Record Program - Lidia Deviga (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
The globalized landscape of healthcare services demands that Medical Record professionals possess proficient English communication skills, particularly in international coding standardizations (ICD-10/ICD-11), patient admissions, and inter-professional reporting. However, non-linguistic healthcare students often face high speaking anxiety and limited classroom exposure. This study evaluates the effectiveness of a Blended Learning model in enhancing the English speaking skills of second-semester Medical Record students at Universitas Bhakti Hasta Mulia Madiun. A quantitative pre-experimental design (one-group pre-test/post-test) was deployed, involving 52 students (40 females and 12 males). The blended framework integrated synchronous face-to-face communicative simulations (medical role-playing) with asynchronous digital platforms (Learning Management System and video-recording tasks). Speaking proficiency was measured using an analytical rubric assessing pronunciation, fluency, grammar, vocabulary, and professional comprehension. Data analysis via paired sample t-test revealed a highly significant improvement from pre-test (M = 62.45) to post-test (M = 78.12), with p < 0.001. Female students demonstrated higher baseline scores, whereas male students exhibited a higher rate of progression. The study concludes that blended learning optimizes pedagogical flexibility, mitigates speech anxiety, and significantly upgrades professional English speaking outcomes in vocational medical contexts.